Laporan Akuntabilitas Dan Transparansi Kinerja Instansi Pemerintah (Studi Kasus Kota Temanggung Jawa Tengah - Widayanti, Ipuk (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2023)
This study aims to determine the accountability and transparency reports on the performance of the Temanggung City Government agencies, Central Java. This research method uses qualitative research with a case study approach. Data collection comes from documentation and interview activities. Interviews were explicitly conducted to find out how the performance accountability reports were interpreted by the Regional Work Units (SKPD) in the Temanggung City Government. The results of this study indicate that the Temanggung City Government agency found several employees who did not understand the concept of accountability for performance. In addition, several problems were found in reporting performance and performance achievements, namely limited human resources, especially APIP, both in terms of quantity and quality. The solution that needs to be done is to improve the internal control system at a better level as a guarantee for the internal control system can reduce the number of irregularities